Self-steem of the arbitrator of professional soccer of the state of Santa Catarina - Renildo Nunes; Viktor Shigunov (Journal of Physical Education (Maringá), 2008)
This descriptive research had the objective of presenting an analysis of the self-esteem thematic concerning the soccer referee position, together with an empiric evaluation of the same category, applied on the board of referees and assistant referees of professional soccer in Santa Catarina. Twenty six subjects, all of them part of the board of CBF (Confederação Brasileira de Futebol), who worked during the 2001 season of Brazilian Championship, were evaluated during the research. One questionnaire containing closed questions about the soccer referee self-esteem was used in the evaluation. The answers showed that both referees and assistant referees present high self-esteem, despite their little knowledge on sport psychology. It was shown that high self-esteem is necessary condition to act as a Brazilian soccer referee.